Truffle biogeography-A case study revealing ecological niche separation of different Tuber species - Gryndler, Milan; Šmilauer, Petr; Šťovíček, Václav; Nováková, Kristýna; Hršelová, Hana; Jansa, Jan (Ecology and evolution, 2017)
Ecology of hypogeic mycorrhizal fungi, such as truffles, remains largely unknown, both in terms of their geographical distribution and their environmental niches. Occurrence of true truffles (Tuber spp.) was therefore screened using specific polymerase chain reaction (PCR) assays and subsequent PCR amplicon sequencing in tree roots collected at 322 field sites across the Czech Republic. These sites spanned a wide range of climatic and soil conditions. The sampling was a priori restricted to areas thought to be suitable for Tuber spp. inasmuch as they were characterized by weakly acidic to alkaline soils, warmer climate, and with tree species previously known to host true truffles. Eight operational taxonomic units (OTUs) corresponding to Tuber aestivum, T. borchii, T. foetidum, T. rufum, T. indicum, T. huidongense, T. dryophilum, and T. oligospermum were detected. Among these, T. borchii was the OTU encountered most frequently. It was detected at nearly 19% of the sites. Soil pH was the most important predictor of Tuber spp. distribution. Tuber borchii preferred weakly acidic soils, T. foetidum and T. rufum were most abundant in neutral soils, and T. huidongense was restricted to alkaline soils. Distribution of T. aestivum was mainly dictated by climate, with its range restricted to the warmest sites. Host preferences of the individual Tuber spp. were weak compared to soil and climatic predictors, with the notable exception that T. foetidum appeared to avoid oak trees. Our results open the way to better understanding truffle ecology and, through this new knowledge, also to better-informed trufficulture.
Keywords: climate; host tree identity; molecular detection; environmental predictors; soil pH